Public health and burnout: a survey on lifestyle changes among workers in the healthcare sector - Petrelli, Fabio; Scuri, Stefania; Tanzi, Elisabetta; Nguyen, Cuc; Grappasonni, Iolanda (Acta Biomedica Atenei Parmensis, 2018)
Burnout Syndrome is a condition which could most commonly be associated with negative effects on the quality of work and life. Some occupations are more likely to suffer from this syndrome, for example workers in the health sector. This survey was therefore conducted among hospital workers of the Marche Region in order to analyze levels of Burnout and any possible correlation of these levels with lifestyle changes. Methods: The survey was carried out using a self-administered, anonymous questionnaire in two sections: the first consisted of the Maslach Burnout Inventory (MBI) and the second contained questions about the healthcare operator’s lifestyle. The MBI investigates levels of Emotional Exhaustion (EE), Depersonalization (DP) and finally of Personal Accomplishment (RP) in respondents. Survey results were processed using descriptive statistics, applying the Chi-square statistic and an Odds Ratio (p